The impact of learning strategy for understanding in get of students of the Fine Arts institute with Art history (Journal of the College of Basic Education, 2022)
This study aimed to know the effect of the leaning strategy for understanding on the achievement of the students of the institute of Fine Arts in subject of Art history and achieve the aim of the research, the research used the experimental method with a signal group, the pre and post tests on a sample of third –year students from the institute of Fine Arts, The research sample consisted of (14) students.The research was a cognitive achievement test (pre and post). To access research results of the research , the researcher used a set of (statistical methods, including: the T-test for two independent samples, and this test was used to equalize the research variables and its ( chronological age- previous experience- intelligence)between members of the experimental and control groups. Paragraph difficultly equation: This equation was used to identify the degree of difficulty of the paragraphs of the achievement test to test effectiveness of the alternative: It was used to effectiveness of incorrect (wrong) alternatives for the items of the achievement test the Alpha Crobanch equation The achievement test was used to calculate achievement test . Coela coefficient and used this equation to calculate the degree of agreement between and use Cohen equation to measure the impact size, and the study showed.1-There are statistically significant differences at the significant level (0,05) between the average ranks of the experimental group students in the pre and post achievement test.2-The superiority of the students who studied the art history curriculum according to the strategy of learning for understanding it is attributed to fact the steps of the learning strategy for understanding contribute to the process of realize events and ideas for students for the longest time.1-There is an effect of the learning for understanding strategy on the cognitive achievement of the experimental group students, based on the results of the study, the researcher recommended several recommendations, including: Emphasizing the necessary of using the learning for understanding strategy in teaching art history developing the cognitive aspect for students.2- teachers must make booklet with modern strategies and methods of teaching.Using modern patterns to keep pace with the educational process and support the teaching process with the capabilities of these patterns in order to deliver the study materials to the minds of students. To complement the current research, the researcher suggests conducting the following studies:1-The effectiveness of the learning strategy for comprehension in other a subjects, focus on a cognitive aspect students of the department of Art Education.2-Learning to understanding strategy and its impact on developing handcrafts skills students of the Departments of Art Education.3- Employing the strategy of learning for understanding in developing critical thinking among students of the institute of Fine Arts in the subject of Arts elements.